The Multiple Facets of Time: Reckoning, Representing, and Understanding Time in Medieval Iceland - Martina Ceolin (Háskóli Íslands, 2020)
This work investigates the multivalent and dynamic portrayal of time in a selec-tion of early Old Icelandic texts from the twelfth and thirteenth centuries. The main objective is to map out the representations of time in terms of the pat-terns conveyed, and to examine how the authors configured time through nar-rative. An extension of this goal is to build up a theoretical understanding of how the people involved in the production of the texts, and possibly their contemporaries as well, reckoned, organized, and understood time. The primary texts analysed for these purposes are Íslendingabók and two Íslendingasögur, Eyrbyggja saga and Laxdæla saga. Íslendingabók is a con-cise history of Iceland from its settlement, ca. 870, to 1118, written by the priest Ari Þorgilsson inn fróði (“the Learned,” 1067/68–1148) between the years 1122–33. The two Íslendingasögur, Eyrbyggja saga and Laxdæla saga, date from the thirteenth century, but, like Íslendingabók, are narratively set in the Settlement Period, although Íslendingabók continues further. The treatment of time in each text, especially the sense of the past, along with the explicit and implicit connections that can be established between the texts, allows for a comprehensive comparative analysis of the time patterns they convey. Along-side this analysis, a focus on the historical period of the writing of the texts leads to a deeper understanding of how medieval Icelanders of that time at once measured, managed, and understood time. This in turn allows for a bet-ter appreciation of the ideological foundations that influenced the representa-tions of time and the mechanisms involved in reconstructing the past in these texts. The analysis is conducted by tackling the issue from different theoretical perspectives: narrative, sociological, and philosophical. Such an analytical ap-proach aims to do justice to the multiplicity of times that concurred in medie-val Iceland. This approach also attempts to bridge gaps that currently exist within this research area, ...